Self-Control Technique to Improve Self-Esteem Among Victims of Bullying - Purnama, Heni; Vina Rahmasari (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Bullying is one of the most common forms of juvenile delinquency and continues to increase every year. Teenagers who are victims of bullying have a high chance of experiencing various health problems such as decreased self-esteem. One way that can be done to increase self-esteem is through self-control techniques. Purpose: This study aimed to determine the effect of virtual self-control on the self-esteem of adolescent victims of bullying. Methods: This study was a quasy experimental with one group pretest posttest design approach. This research was conducted in July 2021, with a total sample of 30 students at senior high school in Bandung City. The sample was selected by using a purposive sampling and the data collection using the Rosenberg Self-Esteem Scale (RSES) questionnaire. Results: Analysis of the characteristics respondents showed that the most of the respondents were female (86.7%) were Muslim (96.7%) and came from the Sundanese (80.0%), with an average age of 17 years, the youngest of the respondent was 15 years old and the oldest was 19 years old. Bivariate analysis showed there was a significant effect of self-control to improve self-esteem of adolescent victims of bullying with t = -31,174, sig = 0.000 (p < α 0.05). Conclusion: The self-control can be used as one of the school programs to deal with adolescent of bullying victim who has low self-esteem by establish counseling. It is hoped that this self-control technique can be used as a form of independent nursing intervention for a nurse in providing nursing care. Nursing Implications: The existence of this study can provide an information related to interventions of victim of bullying who had low self esteem